2019
DOI: 10.7752/jpes.2019.s3143
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objective: to develop the principles of integrated development of speed-power qualities and Jump Shot Accuracy in basketball players 12-13 years old. Material and methods. The experiment involved 20 basketball players who were divided into two groups-experimental and control, each with 10 people. In the control group, the classes were conducted according to the traditional method, and in the experimental group additional exercises on jumping ability and basketball technique were introduced. Pedagogical observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The effectiveness of the training process for high-profile basketball players depends on a properly organized basic stage of training aimed at ensuring the physical and technical fitness of young athletes (Cieślicka et al, 2019;Erčulj, Blas, Bračič, 2010). The study of morphological features, in accordance with the requirements of the sport, the determination of sensitive periods of development of basic physical qualities, the diagnosis of the ability to learn various exercises, allow trainers to select, optimally combine and, if necessary, adjust training tools and #0# Comparison, Assessment of the Relations of Anthropometric and Motor Characteristics of Basketball Players However, only a few studies examined the relationships between physical and special fitness in groups of young athletes (Cieślicka et al, 2019;El-Shafee, Kapouh, 2016;Kozina et al, 2018). In the context of our study, the data of El-Shafee, Kapouh (2016) are important, which reported a significant positive correlation between the indices of coordination abilities and basic basketball skills in 12-year-old athletes.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the training process for high-profile basketball players depends on a properly organized basic stage of training aimed at ensuring the physical and technical fitness of young athletes (Cieślicka et al, 2019;Erčulj, Blas, Bračič, 2010). The study of morphological features, in accordance with the requirements of the sport, the determination of sensitive periods of development of basic physical qualities, the diagnosis of the ability to learn various exercises, allow trainers to select, optimally combine and, if necessary, adjust training tools and #0# Comparison, Assessment of the Relations of Anthropometric and Motor Characteristics of Basketball Players However, only a few studies examined the relationships between physical and special fitness in groups of young athletes (Cieślicka et al, 2019;El-Shafee, Kapouh, 2016;Kozina et al, 2018). In the context of our study, the data of El-Shafee, Kapouh (2016) are important, which reported a significant positive correlation between the indices of coordination abilities and basic basketball skills in 12-year-old athletes.…”
Section: Introductionmentioning
confidence: 99%